Evaluation of Land Suitability for Cempedak (Artocarpus campeden Spreng) in Batu Mandi and South Paringin Districts, Balangan Regency, South Kalimantan - Muhammad Rayhan Ghiffari; Nurlaila Nurlaila; Nukhak Nufita Sari; Andin Muhammad Abduh; Ronny Mulyawan; Hikma Ellya; Rila Rahma Apriani (The University of Lampung, 2026)
Land quality is a key determinant of fruit production, supporting nutrient supply, food security, and sustainable agriculture. This study evaluates potential changes to land suitability classes to improve land-use planning and spatial rearrangement, notably to support the development of cempedak cultivation in Batu Mandi and South Paringin Districts, Balangan Regency, South Kalimantan Province. The research was conducted from May to August 2025 using a matching method to link land characteristics to suitability criteria for cempedak, and the results were presented as ArcGIS maps. Results show both districts have considerable potential for cempedak development, although current conditions fall within unsuitable (N) and marginally suitable (S3) classes. In Batu Mandi District, actual suitability is S3 covering 11,238.48 ha, and N covering 1,541.61 ha. In South Paringin District, cempedak suitability is also S3, covering 6,953.21 ha. The main limiting factors include unsuitable soil texture, low base saturation, acidic soil pH, and low nutrient availability of P₂O₅ and K₂O. Improvement efforts involving adding pelleted compost and liming with high cultivation, and fertilising with moderate cultivation of triple superphosphate and KCl potentially increase suitability from S3 to S2 or even S1. Therefore, the land has the potential to become a cempedak planting area and produce maximum productivity.